2018
DOI: 10.1080/15384101.2017.1407895
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA ZFAS1 sponges miR-484 to promote cell proliferation and invasion in colorectal cancer

Abstract: The incidence and mortality rate of colorectal cancer (CRC) have been significantly increasing. However, mechanisms involved in CRC progression are still unclear. LncRNA ZFAS1 has been verified as oncogenic molecular in a series of tumors, including CRC. However, the underlying mechanism of ZFAS1 in CRC carcinogenesis remains unclear. In the present study, our data showed that ZFAS1 expression was significantly upregulated in CRC tissues and cell lines. Correlation analysis showed that high ZFAS1 expression wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 24 publications
2
52
0
Order By: Relevance
“…For instance, ZFAS1 interacted with miR‐150‐5p to regulate the expression of transcription factor Sp1, thereby regulating proliferation rate, migration activity and development of chemoresistance in epithelial ovarian cancer . ZFAS1 sponged miR‐484 to regulate cell proliferation and invasion in colorectal cancer cells and modulate tumour growth in nude mice . In addition, ZFAS1 served as an oncogene in bladder cancer tumorigenesis by sponging miR‐329 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ZFAS1 interacted with miR‐150‐5p to regulate the expression of transcription factor Sp1, thereby regulating proliferation rate, migration activity and development of chemoresistance in epithelial ovarian cancer . ZFAS1 sponged miR‐484 to regulate cell proliferation and invasion in colorectal cancer cells and modulate tumour growth in nude mice . In addition, ZFAS1 served as an oncogene in bladder cancer tumorigenesis by sponging miR‐329 …”
Section: Discussionmentioning
confidence: 99%
“…26 ZFAS1 sponged miR-484 to regulate cell proliferation and invasion in colorectal cancer cells and modulate tumour growth in nude mice. 27 In addition, ZFAS1 served as an oncogene in bladder cancer tumorigenesis by sponging miR-329. 28 In the current study, the miR-432-5p was predicted as a target of ZFAS1.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Zinc nger antisense 1 (ZFAS1) is a novel tumor-related lncRNA that has been identied as an oncogene in the development of multiple human cancers. [12][13][14] Previous studies had demonstrated that ZFAS1 was abnormally expressed in AML, and ZFAS1 overexpression promoted AML progression through acting as a sponge for miR-150. 15,16 A recent document manifested that ZFAS1 promoted cervical cancer cell chemoresistance to cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…Fu et al (9) indicated that long intergenic non-protein coding RNA (LINC)00210 drives Wnt/β-catenin signaling activation and liver tumor progression in a catenin β interacting protein 1-dependent manner. In addition, Xie et al (10) indicated that lncRNA zinc finger NFX1-type containing 1 antisense RNA 1 sponges miR-484 to promote cell proliferation and invasion in CRC. Therefore, it has been widely acknowledged that lncRNAs have essential roles in human cancer, including CRC.…”
Section: Introductionmentioning
confidence: 99%